Sugarcane Cultivar Descriptive Fact Sheet: CPCL 02-6848 and CPCL 05-1201 - Hardev Sandhu; Wayne Davidson (EDIS, 2018)
CPCL 02-6848 and CPCL 05-1201 are emerging sugarcane cultivars in Florida. Both cultivars were released commercially in 2012 and were quickly adopted by local sugarcane growers because of high yields and moderate to high resistance against major sugarcane diseases in Florida. This 4-page fact sheet provides basic information and yield and disease information to assist growers in management of these cultivars. Written by Hardev Sandhu and Wayne Davidson, and published by the UF/IFAS Agronomy Department, March 2018. http://edis.ifas.ufl.edu/sc104